2012
DOI: 10.1007/s11248-012-9666-3
|View full text |Cite
|
Sign up to set email alerts
|

The polyamine spermine protects Arabidopsis from heat stress-induced damage by increasing expression of heat shock-related genes

Abstract: It is known that the polyamine (PA) biosynthetic pathway is modulated at the transcriptional level during abiotic stresses. Here we studied the expression of PA biosynthetic pathway genes upon exposure to heat shock (HS) in Arabidopsis and showed that the spermine (Spm) synthase gene (SPMS) and S-adenosylmethionine decarboxylase 2 gene are induced at the earliest stage, followed by the induction of the arginine decarboxylase 2 gene. Correspondingly, Spm content increased linearly upon HS, and putrescine (Put) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(91 citation statements)
references
References 36 publications
5
84
0
1
Order By: Relevance
“…Nevertheless, many genes responded similarly in these genotypes, such as genes involved in the biosynthesis of jasmonic acid and abscisic acid, jasmonic acid-and salicylic acid-responsive genes, receptorlike kinases, mitogen-activated protein kinases, genes with a role in calcium regulation, or the genes of transcriptional factors [30]. As also observed for other polyamines, an elevated spermine level in Arabidopsis plants upregulated genes encoding heat shock transcription factors and heat shock proteins after exposure to high temperature [42]. Transcripts of antioxidant enzymes, such as ascorbate peroxidase, manganese superoxide dismutase and glutathione-S-transferase, were also induced more significantly by abiotic stressors, such as salt, cold or acidic stress, in tobacco plants overexpressing carnation SAMDC [43] (Table 1).…”
Section: Sperminementioning
confidence: 71%
See 1 more Smart Citation
“…Nevertheless, many genes responded similarly in these genotypes, such as genes involved in the biosynthesis of jasmonic acid and abscisic acid, jasmonic acid-and salicylic acid-responsive genes, receptorlike kinases, mitogen-activated protein kinases, genes with a role in calcium regulation, or the genes of transcriptional factors [30]. As also observed for other polyamines, an elevated spermine level in Arabidopsis plants upregulated genes encoding heat shock transcription factors and heat shock proteins after exposure to high temperature [42]. Transcripts of antioxidant enzymes, such as ascorbate peroxidase, manganese superoxide dismutase and glutathione-S-transferase, were also induced more significantly by abiotic stressors, such as salt, cold or acidic stress, in tobacco plants overexpressing carnation SAMDC [43] (Table 1).…”
Section: Sperminementioning
confidence: 71%
“…These mechanisms make it unnecessary or of secondary importance for polyamines to participate in direct protection. Indeed, small changes in polyamine Arabidopsis [42] genes involved in flavonoid and/or lignin biosynthesis, such as phenylalanine ammonia lyase 1 Exogenous polyamine putrescine heat shock protein 17 gene wheat [31] spermidine photosystem II D1 protein gene Xanthoria parietina [36] spermidine genes involved in primary metabolism, signal transduction, hormone responses tomato [35] genes of transcription factors genes involved in energy metabolism, cell wall metabolism, and photosynthesis spermidine β-amylase gene white clover [37] spermine heat shock protein genes trifoliate orange [41] abscisic acid (ABA)-responsive element binding factor (ABF) gene gibberellins; GABA: -aminobutyric acid).…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…In rice seedlings, the expression of HSP17.4 was up-regulated during the seedling and anthesis stages in response to heat stress (Chen et al, 2014). In Arabidopsis, up-regulated levels of HSP17.6 were detected under heat stress (Sagor et al, 2013). Györgyey et al (1991) isolated cDNA clones (MsHSP18-1) from alfalfa (Medicago sativa) and found that MsHSP18-1 transcription was induced by elevated temperature.…”
Section: Hsps Are Involved In Heat Tolerance In Grape Leaves Through mentioning
confidence: 99%
“…This assumption is supported by the 2.1-fold increase in abundance of spermidine synthase SPD1 after 24 h HS (Supplemental Data Set 2). When exogenously applied, spermidine was shown to protect Arabidopsis seedlings from HS (Sagor et al, 2013).…”
Section: Metabolic Remodeling Early After Onset Of Hs Is Also Charactmentioning
confidence: 99%